Proses perubahan harapan ibu dengan anak terlambat bicara - Haerani Nur (Seminar Nasional LP2M UNM, 2019)
Hope is one of the psychological attributes that can help mothers with speech delay children in facing difficult conditions related to handling children and concerns about the children’s future. Nevertheless, study of the concept of hope in children with developmental delays context is still very limited. This study aims to produce a theoretical model of the dynamics of mothers hope of children with speech and language developmental delays, which are formulated using a grounded theory approach. The results of this study found a number factors in forming and inhibiting realistic hope, as well as theoretical explanations about the process of forming the mother's realistic hope to the child's future. This adds insight into the concept of hope in the study of psychology, as well as being the basis in formulating a number of intervention programs in handling children with speech-language developmental delay.